Acute Myeloid Leukemia and the Bone Marrow Niche—Take a Closer Look - Behrmann, Lena; Wellbrock, Jasmin; Fiedler, Walter (Frontiers in Oncology, 2018)
The bone marrow is the home of hematopoiesis and is therefore a hotspot for the development of hematopoietic diseases. Complex interactions between the bone marrow microenvironment and hematopoietic stem cells must find a balance between proliferation, differentiation and homeostasis of the stem cell compartment. Changes in this tightly regulated network can provoke malignant transformation, leading to hematopoietic diseases. Here we focus on acute myeloid leukemia (AML), since this is the most frequent acute leukemia in adulthood with very poor overall survival rates and where relapse after chemotherapy continues to be a major challenge, driving demand for new therapeutic strategies. Current research is focusing on the identification of specific interactions between leukemic blasts and their niche components, which may be exploited as novel treatment targets along with induction chemotherapy. Significant progress has been gained over the last few years in the field of high-resolution imaging. Confocal ex vivo and intravital microscopy have revealed a detailed map of bone marrow structures and components; as well as identifying numerous alterations in the stem cell niche that correspond to disease progression. However, the underlying mechanisms are still not completely understood and due to the complexity, their elucidation remains a challenging. This review discusses the constitution of the AML niche in the bone marrow, the improvement in visualization of the complex three-dimensional niche structures and points out new therapeutic strategies to increase the overall survival of AML patients.